OIs Pruebas internacionales, medios, redes y la educación en Argentina / IOs, International tests, mass media, social networks and the education in Argentina - Caldo, Martín (Journal of Supranational Policies of Education (JOSPOE), 2016)
ABSTRACT This work tries to reflect on international exams, especially the PISA test and the way it inserts itself into the big population groups due to the power that the mass media and the social networks have been gaining lately, allowing these latter to impose the topics for discussion. It is thought that these information transmission devices complement each other, installing powerful political ideas that strike on the public opinion . Because of this, it is very difficult to install public educational policies whose aims differ from those of the PISA exam. In this article, three approaches are introduced> First, a description of the situation in Argentina , based on the test results of the year 2012, secondly, the analysis of two political parties responses towards the data provided by the media ,and finally, a possible alternative to construct another way of thinking the education that combines the participation presencial with the virtual one that the networks provide. Key words: Evaluations PISA, mass media, social networks, educational politic RESUMEN Este trabajo intenta reflexionar sobre las evaluaciones internacionales, en especial la prueba PISA y su penetración en las grandes capas poblacionales a partir del poder de imposición de agendas de discusión que van adquiriendo los medios de comunicación y las redes sociales. Se sostiene que la combinación de estos dispositivos de transmisión de la información actúan en forma complementaria instalando potentes discursos que impactan sobre el sentido común y resulta muy complejo establecer políticas públicas educativas que se dirijan en direcciones diferentes. Se propone la descripción de la situación en la República Argentina a partir de la difusión de datos de la pruebas PISA desarrolladas en el año 2012, el análisis de dos respuestas políticas diferentes ante esta lectura de los datos planteada por los medios, cerrándose el artículo con una posible alternativa para construir otra forma de pensar la educación que combine la participación presencial con la virtual que proporcionan las redes. Palabras clave: Pruebas PISA, medios, redes, política educativa